The problems of developing restaurant business in Kazakhstan - Batyrova, N.T.; Mombekova, G.R.; Yerzhanova, S.K.; Huszti, Zh. (BUKETOV BUSINESS REVIEW, 2018)
This article explores the restaurant business in Kazakhstan, which takes a special place in increasing revenue sources by attracting external visitors to the country. This is due to the possibility of timely and immediate investigation of the restaurant business market. Currently, in connection with the crisis, it is difficult to say that eating out, in restaurants and cafes is in great demand and is in the first place. Therefore, because of the consequences of the crisis, people began to save on food outside the house. The lack of staff and qualified personnel, the lack of modern culinary schools, above all, the transition from the Soviet catering, which ruled the country until the times of independence, to modern conditions of public catering is not easy, besides it requires a qualification technique and a specialized approach. The problematic aspects of management and marketing of the restaurant business area deserve a scientific interest, therefore this article is an actual scientific research of novelty and scientific and practical importance. The conducted analysis to identify the problematic aspects of the development of the public catering sector will allow management to make more effective decisions when planning the future activities of catering establishments where there is a high probability of success in the restaurant business. The developed proposals can be used to create state targeted marketing and organizational programs for the development and improvement of the restaurant business and the resolution of problematic parties.